Organisation du travail en Russie postsoviétique - Valery Krylov; Jean-Luc Metzger (Recherches Sociologiques et Anthropologiques, 2009)
If there exists a particularly relevant configuration for analysing the circulation of imported management arrangements, it is indeed that of a country whose economies are said to be in transition. With this in view, the authors examine, regarding Russia, how decisions of macro-economic policies, called “shock therapies”, have turned out in terms of imported management arrangements, and how the latter cause tension with specific practices perfected during the soviet period. Basing their analysis on empirical inquiries done in six enterprises soon after 2000, the authors show the extent to which the will to implement certain characterisics of neo-management are singularly reminiscent of characterisics of “homo sovieticus”, thus reinforcing “traditional practices”, where arbitrary managerialism, clanism and Taylorism mingle.